2010
DOI: 10.1007/s00059-010-3355-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering von Herzklappen und Myokard

Abstract: Cardiac function, including the heart muscle and valves, can be severely altered by congenital and acquired heart diseases. Several graft materials are currently used to replace diseased cardiac tissue and valvular segments. Implantable grafts are either non-vital or can trigger an immune response which leads to graft calcification and degeneration. None of the existing grafts have the ability to remodel and grow in tandem with the physiological growth of a child and therefore require re-operation. Novel appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 78 publications
0
4
0
2
Order By: Relevance
“…[11,12] Successful preclinical studies using prosthetic valve leaflets and swine intestinal submucosa conduits seeded with autologous endothelial cells (ECs)/endothelial progenitor cells (EPCs) [13,14] have been followed by first-in-human studies that confirmed feasibility and advantages of endothelialized grafts. [15,16] Despite the observed improvements of this conduit endothelialisation strategy, the physiological characteristics remained suboptimal in comparison to native vessels, due to the lack of vascular smooth muscle cells (VSMCs). VSMCs are crucial in vessel structure and function; nonetheless, few studies have tested the in vivo potential of tissue-engineered vascular grafts (TEVG) repopulated with VSMCs.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Successful preclinical studies using prosthetic valve leaflets and swine intestinal submucosa conduits seeded with autologous endothelial cells (ECs)/endothelial progenitor cells (EPCs) [13,14] have been followed by first-in-human studies that confirmed feasibility and advantages of endothelialized grafts. [15,16] Despite the observed improvements of this conduit endothelialisation strategy, the physiological characteristics remained suboptimal in comparison to native vessels, due to the lack of vascular smooth muscle cells (VSMCs). VSMCs are crucial in vessel structure and function; nonetheless, few studies have tested the in vivo potential of tissue-engineered vascular grafts (TEVG) repopulated with VSMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Hierzu wird auch auf die Beiträge in Herz, Heft 5 verwiesen, die sich mit allgemeinen Aspekten (Maisch [134]) und der gezielten, meist chirurgischen Anwendung verschiedener Zellpopulationen der Regenerationstherapie befassen (Bergmann et al [135], Cabotari et al [136], Kaminski et al [137] (2007) …”
Section: Schlussfolgerungunclassified
“…Kaminski et al [7] favorisieren die intramyokardiale Stammzelltherapie; Cebotari und Haverich [3] berichten über beeindruckende erste Erfolge beim "Tissue-Engineering von Herzklappen und Myokardgewebe". Becher et al [1] beschreiben "EC-like cells und endothelial outgrow cells (EOCs)" als Teil einer zeitlich begrenzten Reendothelialisierung der Läsion und als Platzhalter der Regeneration an der geschädigten Gefäßwand.…”
Section: Regeneration In Der Kardiologie -Innovation Oder Illusion?unclassified